5x-9+7=3

Simple and best practice solution for 5x-9+7=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-9+7=3 equation:


Simplifying
5x + -9 + 7 = 3

Reorder the terms:
-9 + 7 + 5x = 3

Combine like terms: -9 + 7 = -2
-2 + 5x = 3

Solving
-2 + 5x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 5x = 3 + 2

Combine like terms: -2 + 2 = 0
0 + 5x = 3 + 2
5x = 3 + 2

Combine like terms: 3 + 2 = 5
5x = 5

Divide each side by '5'.
x = 1

Simplifying
x = 1

See similar equations:

| 6x+5.4=19 | | 13-(4m+5)=4+2m-14 | | 10=-6.9+a | | 6(6x-1)=41 | | 4+3(2r+-8)=28 | | 2(4-9)-5= | | 2/7v-4/3=-3/2 | | x+(-3)=7 | | 4x+6=12-10x | | 5b+10b=9 | | 5(b-1)=25 | | -6.4=6 | | 135=10x+65 | | 4x(10+6)= | | 2(4-9)+10= | | 40x+51=40x+46 | | 5x-20y=10 | | 2(4-9)+-10= | | 8n+4=8n-24 | | y=4c-3(c+2) | | 7w+5y=-13 | | 2(4-9)= | | 11+3p=5 | | 2(1+-4x)+3=45 | | 11n+2=35 | | -6(x+4)=23 | | x-24=12 | | -5y+11=31y | | 7-(5-8x)=4x+3x | | 2y-7=-12y-6 | | 3x+10y=25 | | 3x^2-17=-130 |

Equations solver categories